2022
DOI: 10.1302/2046-3758.115.bjr-2021-0537.r1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effect of anatomical tibial component design on load distribution of medial proximal tibial bone in total knee arthroplasty

Abstract: Aims This study aimed to identify the effect of anatomical tibial component (ATC) design on load distribution in the periprosthetic tibial bone of Koreans using finite element analysis (FEA). Methods 3D finite element models of 30 tibiae in Korean women were created. A symmetric tibial component (STC, NexGen LPS-Flex) and an ATC (Persona) were used in surgical simulation. We compared the FEA measurements (von Mises stress and principal strains) around the stem tip and in the medial half of the proximal tibial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Some finite element modeling studies have found higher tibial bone stresses with porous tibial components [ 37 , 38 ]. Other studies have shown that differences in tibial platform design result in different stresses on the bone [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some finite element modeling studies have found higher tibial bone stresses with porous tibial components [ 37 , 38 ]. Other studies have shown that differences in tibial platform design result in different stresses on the bone [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the walking loading conditions from our previous study were applied to validate the FE model. 22 Second, the FE model was validated by applying stand-up loading conditions corresponding to activities of daily living for a 0-degree flexion angle of the knee. 23 Third, a compressive loading condition corresponding to clinical relevance was used to evaluate the effect of the three stem lengths on various bone defects.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, three loading conditions were included: two for the validation of the FE model and one for model predictions for clinically relevant loading scenarios. First, the walking loading conditions from our previous study were applied to validate the FE model 22 . Second, the FE model was validated by applying stand-up loading conditions corresponding to activities of daily living for a 0° flexion angle of the knee 23 .…”
Section: Loading and Boundary Conditionsmentioning
confidence: 99%
“…Most of the body's weight is held up by two bone joints. The joint between the patella and the femur allows forces from the quadriceps femoris to pass over the knee without causing friction [2]. The knee's medial ligament complex is made up of one large ligament, a group of thickenings and tendon attachments on the kneecap.…”
Section: Introductionmentioning
confidence: 99%